Pembuatan Kombucha dengan Berbagai Nutrisi - Shefira Adistyaningrum; Lusiana Aliah Nur Rahmah; Achmad Khoirul Mustain; Fara Aulia Astitiningrum; Rizki Ayu Lestari; Nabella Devy Izhmi; Siti Listiana Wulandari; Nuri Isnaini (Pusat riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of nutrient types on kombucha fermentation using Sosro Tea as a medium. The practicum was conducted with two variations, namely honey as a natural nutrient and Tropicana Slim as a low-calorie sweetener. Parameters observed included color changes, aroma, SCOBY layer formation, pH, and microbial contamination. The results showed that fermentation using honey produced the best combination, which was characterized by a brighter color change, a stable sour aroma, the formation of a thick and pure white SCOBY, and a stable pH of around 4. In contrast, fermentation using Tropicana Slim failed to achieve optimal results. This low-calorie sweetener cannot be metabolized by microbes, resulting in a thin SCOBY and the appearance of green-black mold. Based on these results, it can be concluded that the success of kombucha fermentation is greatly influenced by the availability of simple sugars, which are the main energy source for the SCOBY. In addition, the culture's resistance to microbial contamination also plays an important role in the fermentation process.